A Microcontroller Based Application of a True Rms Value Scale System - Gencer, Cetin (Gazi Univ, 2009)
This study provides an overview of an application of a true RMS value scale system by PIC 16F876 microcontroller. In power control systems, to get the RMS value of an alternative voltage is very important. In case of the voltage being applied to charge is sinusoid, the measurement of the voltage and transferring it to the valuing module are performed by simple circuit arrangements. However, deformations of sinus signal or control operations relating phase angle, to measure the voltage applied to charge and to transfer it to the valuing module pose a problem. Particularly in power control circuits relating phase angle, the output voltage is expected to be stable. In these sorts of systems, acquiring a stable output voltage is feasible via pretty fast and accurate measurement results. This paper sets its sights on developing a microcontroller based true RMS value scale system which will be used in control systems deleted to the phase angle, which can measure with sensitivity of average %0,4 and which is convenient for using in high power applications.
Keywords: True RMS value; Microcontroller; PIC 16F876